Philosophy in the Islamic tradition: implications for the philosophy for children(P4C) Program - Hashim, Rosnani (Peter Lang, 2010)
The work described in this book represents the latest research on theoretical concepts and applied projects within this field and brings together contributions from twenty-nine countries, representing all continents. The authors address questions on the theoretical foundation of Philosophy for Children, the application of philosophical methods, the community of inquiry, international and national didactical concepts as well as the evaluation of those concepts. A primary goal of this book is to enhance intercultural academic exchange and to encourage further research and practical work in this field.